Benign paroxsymal positional vertigo – recommendations for treatment in primary care - Wang YH; Chan CY; Liu QH (Dove Medical Press, 2019)
Yi-Hong Wang,1,* Ching Yee Chan,2,* Qing-Hua Liu11Department of Otorhinolaryngology, The Shengli Clinical Medical College of Fujian Medical University, Fujian Provincial Hospital, Fuzhou, People’s Republic of China; 2Department of Otolayngology, KK Women’s and Children’s Hospital, Duke-NUS Medical School, Singapore*These authors contributed equally to this work Background: Benign paroxysmal positional vertigo (BPPV) is a common cause of vertigo that can be easily diagnosed and treated in primary care.Purpose: We describe our experience with a large cohort of patients and include recommendations for diagnosis and treatment in the primary care setting.Patients and methods: Three hundred and fifty-nine patients were diagnosed with BPPV between June 2011 and March 2017 at the dizziness clinic of Fujian Provincial Hospital, Fuzhou, China. We mainly used Epley’s maneuver and barbecue roll for the treatment of PSC-BPPV and HSC-BPPV respectively.Results: Our results show that posterior semicircular canal (PSC) involvement is the most common (n=264, 73.5%), followed by horizontal semicircular canal (HSC, n=81, 22.5%) and multicanal (n=12, 3.3%) involvement. Anterior semicircular canal (ASC) BPPV is the rarest (n=2). Particle repositioning maneuvers (PRM) are the treatment of choice and have a high success rate (1 month after treatment), from 75% (9 out of 12) for multicanal to 95.8% (253 out of 264) for PSC, and to 100% for HSC and ASC involvement respectively.Conclusion: We recommend the use of the Epley’s maneuver and barbecue roll for the treatment of PSC-BPPV and HSC-BPPV, respectively. Patients should be reviewed regularly and repeated maneuvers can be performed. Unresolving symptoms require tertiary evaluation.Keywords: giddiness, benign paroxysmal positional vertigo, Epley’s maneuver, diagnosis, treatment